Pattern Formation at Interfaces - Colinet, Pierre; Nepomnyashchy, Alexander; SpringerLink (Online service) (Vienna : Springer Vienna, 2010)
The book deals with modern methods of nonlinear stability theory applied to problems of continuous media mechanics in the presence of interfaces, with applications to materials science, chemical engineering, heat transfer technologies, as well as in combustion and other reaction-diffusion systems. Interfaces play a dominant role at small scales, and their correct modeling is therefore also crucial in the rapidly expanding fields of microfluidics and nanotechnologies. To this aim, the book combines contributions of eminent specialists in the field, with a special emphasis on rigorous and predictive approaches. Other goals of this volume are to allow the reader to identify key problems of high scientific value, and to see the similarity between a variety of seemingly different physical problems.
Interfacial patterns and waves in liquid layers and thin films -- Nonlinear dynamics of fronts -- Three Dimensional Film Dynamics -- Thin Film and Droplet Patterns Shaped by Surface Forces -- Interfacial Phenomena in Materials Science -- The Physics and Analyses of Interfacial Instabilities that Arise from Phase Change.
Keywords: Engineering; Hydraulic engineering; Engineering; Engineering Fluid Dynamics